OCCURRENCE OF MULTIPLE INFECTIONS IN CATTLE AT A FARM IN THE CIBIRU AREA, WEST JAVA - Putri, Risti Yupiesta; Permadi, Anindya Putri; Sevaot, Amar Adonay; Cyntia, Annisa Permana; Windria, Sarasati; Krissanti, Ita; Satrio, Faisal Amri; Septiyani; Prayugo, Armanda Dwi (Buletin Veteriner Udayana, 2026)
The health of beef cattle is a crucial aspect of livestock management. Effective health management in cattle serves to minimize potential economic losses caused by diseases that commonly affect beef cattle. These diseases may be caused by bacteria, fungi, viruses, as well as blood and gastrointestinal parasites. Multiple infections may occur, particularly when suboptimal animal conditions and environmental factors support disease transmission. This case report aims to describe the occurrence of multiple infections and to identify the causative infectious agents in a beef cattle farm located in Cibiru, West Java. The case involved a 4-year-old Limousin cow that exhibited clinical signs including nasal discharge, hypersalivation, diarrhea, and tick infestation. Samples collected for diagnostic examination included nasal discharge swabs, blood, and fecal samples. Nasal swab samples were cultured on blood agar plates (BAP) and MacConkey agar (MCA), followed by primary tests including Gram staining, catalase test, coagulase test, and biochemical tests. Blood samples were examined using blood smear evaluation and differential leukocyte counts. Fecal samples were examined using native smear, flotation, sedimentation, and McMaster techniques. The results revealed a case of multiple infections, with the identification of Staphylococcus aureus and Klebsiella pneumoniae, as well as a gastrointestinal parasitic infection (coccidiosis). In addition, infestation with Rhipicephalus ticks contributed to blood parasitic infections, including babesiosis and anaplasmosis. These concurrent infections were associated with a compromised immune status and reduced production performance, potentially leading to economic losses for the farmer. Therefore, preventive and control measures, including proper sanitation and biosecurity, are essential, as infected animals and contaminated environments may act as sources of disease transmission.